LOCAL GOVERNANCE: THE ROLE OF FISCAL TRANSFERS AND REGIONAL INNOVATION ON PROVINCIAL FISCAL INDEPENDENCE IN INDONESIA - Setio Rini; Sri Maryati; Edi Ariyanto (FAKULTAS EKONOMI DAN BISNIS UNIKARTA, 2026)
Regional fiscal independence is a key indicator of fiscal decentralization performance in Indonesia. The objective of this study is to estimate the influence of the General Allocation Fund (DAU), Revenue Sharing Fund (DBH), Regional Innovation Index (IID), and Gross Regional Domestic Product (GRDP) on the fiscal independence of 34 provinces in Indonesia for the 2021 - 2025 period. This study is quantitative and uses panel data. Data collection methods include accessing sources from the Ministry of Finance, Statistics Indonesia (BPS), and the Ministry of Home Affairs, and are processed using panel data analysis. The estimation applies a series of diagnostic tests including the Chow, Hausman, Breusch-Pagan LM, Wooldridge, and Pesaran (Cross-Sectional Dependence) tests to ensure the accuracy of the estimates and model determination. The baseline Random Effects estimation shows that DBH has a negative and significant association with fiscal independence, while the Regional Innovation Index and GRDP have positive and significant associations. However, robustness checks using Fixed Effects and lagged GRDP specifications indicate that GRDP is the most consistent determinant of fiscal independence, whereas the estimated effects of DBH and regional innovation are sensitive to model specification. The General Allocation Fund (DAU) has a negative but statistically insignificant association with fiscal independence. These findings have strong policy implications for strengthening regional innovation capacity and increasing local economic productivity as a strategy towards sustainable fiscal independence during the implementation of Law Number 1 of 2022.